1975
DOI: 10.1210/jcem-40-2-326
|View full text |Cite
|
Sign up to set email alerts
|

Serum Thyroid Hormone and Thyrotropin Levels in Subjects from Endemic Goiter Regions of New Guinea

Abstract: We studied serum thyroid hormone and thyrotropin (TSH) levels in subjects from two regions (Nomane and KarKar) of New Guinea where endemic goiter and/or iodine deficiency are prevalent. The results of the studies in 285 patients from Nomane indicated subnormal serum T4 (mean plus or minus SD, 6.5 plus or minus 2.8 vs 8.4 plus or minus 2.0 mug/1ll ml, for normal Americans, P less than 0.001), supranormal serum T3 (161 plus or minus 51 vs 126 plus or minus 33, ng/100 ml, p less than 0.001), supranormal serum T3/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
3

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 0 publications
10
37
3
Order By: Relevance
“…Thus, in moderate iodine de®ciency, a reduced serum TSH is observed compared with serum TSH in areas with a lesser degree of iodine de®ciency or iodine suf®ciency. These reduced TSH levels especially among the elderly are in contrast to increased TSH as a direct effect of iodine de®ciency as observed in severe iodine de®ciency (20). This is presumably due to autonomous functioning thyroid tissue, as this regional difference in serum TSH was only found in subjects with nodular glands, and it is in accordance with data from moderate iodine de®ciency in Italy, where decreasing levels of serum TSH were found with increasing degrees of goitre at a clinical examination (21).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, in moderate iodine de®ciency, a reduced serum TSH is observed compared with serum TSH in areas with a lesser degree of iodine de®ciency or iodine suf®ciency. These reduced TSH levels especially among the elderly are in contrast to increased TSH as a direct effect of iodine de®ciency as observed in severe iodine de®ciency (20). This is presumably due to autonomous functioning thyroid tissue, as this regional difference in serum TSH was only found in subjects with nodular glands, and it is in accordance with data from moderate iodine de®ciency in Italy, where decreasing levels of serum TSH were found with increasing degrees of goitre at a clinical examination (21).…”
Section: Discussionsupporting
confidence: 84%
“…[17][18][19] In the present study we found higher TSH levels in goitrous subjects than in nongoitrous ones.…”
supporting
confidence: 53%
“…This could explain the circumstances in the iodine-deficient rat where an apparently euthyroid state is associated with a low plasma T4, normal plasma T3, and an elevated TSH (17,43). Similar arguments can be applied to explain why patients with endemic goiter, a high plasma TSH, and normal plasma T3 can appear euthyroid as well as why patients with early thyroid dysfunction with reduced plasma T4, normal plasma T3, and elevated TSH are often asvmptomatic in metabolic terms (44)(45)(46)(47). It would appear that the presence of a system in the thyrotroph responsive to decreases in either plasma T, or T4 would provide maximum protection against the onset of metabolic hypothyroidism in tissues such as the liver and kidney whether the threat to the euthyroid state is a result of primary thyroid disease or iodine deficiency.…”
Section: Specific Experimetital Protocolsmentioning
confidence: 91%